Examining the Inverted U-Shaped Relationship Between Benevolent Leadership and Employees’ Work Initiative: The Role of Work Engagement and Growth Need Strength - Li, Huan; Sun, Saisai; Wang, Pu; Yang, Yating (Frontiers in Psychology, 2022)
Benevolent leadership is generally considered to be beneficial for work initiative. However, based on social exchange theory, this paper explores an inverted U-shaped relationship between benevolent leadership and work initiative. Using a multilevel structural equation model that analyzed data from 596 employees and 139 supervisors in multiple technology companies, our findings show that benevolent leadership had an indirect, negative curvilinear relationship with work initiative via work engagement at both the individual and team levels. Furthermore, we also indicate that growth need strength moderates the positive relationship between benevolent leadership and work engagement at the individual level. Theoretical and practical implications and future research directions are discussed.